The Urgency of Linguistic Skills to Read Kitab Tafsir in Boarding Schools in Indonesia: Analysis of Students’ Learning Issue - Namira, Silva; Wiza, Rahmi; Huda Binti Mohd Nadhir, Nazratul; Alhabib, Alhabib (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2023)
The study is aimed at investigating learners’ issues on reading kitab tafsir in boarding schools in Indonesia. This study employs the case study approach of the qualitative method. Data is collected through in-depth interviews with ten informants (teachers and learners) selected by using purposive sampling technique. The data is thematically analyzed by using interactive analysis technique of Miles & Huberman model of NVivo 12. The findings of the study reveal that there are nineteen learners’ linguistic issues to understand the kitab tafsir. All issues are grouped into four categories, namely: two issues are related to ashwat (phonology), six issues are connected to sharaf (morphology), six issues are about nahwu (syntax), and other five issues are related to dilalah (semantic). All issues revealed in the study are crucial to be solved to understand the kitab tafsir in boarding schools all over Indonesia. Thus, teachers should be creative to find interesting and innovative learning techniques so that reading the kitab tafsir is no longer an issue for learners. The nineteen issues are deeply and comprehensively analyzed and discussed in the article.